(untitled) (Czech Journal of International Relations, 2024)
This article reflects on Rola El-Husseini’s critique of the Western double standards concerning women’s rights and religious freedom in her work "Double Standards and Dissonance: Women’s Rights and Freedom of Religion in the Global North." It expands on the concept of "gender-washing," illustrating how both left- and right-wing authoritarian regimes exploit gender equality rhetoric for political gains without genuine efforts toward equality. Through examples from Czechoslovakia and contemporary India, the article explores how different ideologies—from Marxism-Leninism to religious nationalism—use women’s rights as a façade while maintaining autocratic control. It also engages with postcolonial feminist critiques of Western universalism.